Consumer Trust as a Missing Link between Digital Marketing Strategies and Purchase Intention in Culinary MSMEs: A Systematic Literature Review - jihan Silvi Tria Perdana; Muhammad Iqbal Fasa; Arifa Kurniawan; Hanif; Moh. Mukri (Dinamis : Journal of Islamic Management and Bussiness, 2026)
This study examines the influence of digital payment, digital promotion, and brand awareness on consumer purchase intention in culinary MSMEs, emphasizing the mediating role of consumer trust. A Systematic Literature Review (SLR) following the PRISMA approach was conducted by synthesizing relevant national and international studies published between 2021 and 2025. The findings indicate that digital payment enhances transaction convenience, efficiency, and security, while digital promotion effectively expands market reach and strengthens consumer engagement. Brand awareness also positively influences purchase intention by increasing consumer recognition and confidence in MSME products. Furthermore, consumer trust consistently mediates the relationships between digital payment, digital promotion, brand awareness, and purchase intention, highlighting its strategic role in digital marketing effectiveness. This study contributes to the digital marketing and MSME literature by providing an integrated understanding of how digital marketing strategies foster consumer purchase intention through trust. The findings also offer practical insights for culinary MSME owners in designing trust-oriented digital marketing strategies to improve competitiveness in the digital economy. Keywords: Digital Payment, Digital Promotion, Brand Awareness, Consumer Purchase Intention.